2017
DOI: 10.1109/tmag.2017.2707527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Ordering on the Stability of Ni–Mn–Ga(–Co–Cu) Alloys Along the Tetragonal Deformation Path

Abstract: The influence of magnetic ordering on the stability of Ni-Mn-Ga(-Co-Cu) Heusler alloys is investigated using the first-principles exact muffin-tin orbital method in combination with the coherent-potential approximation. The paramagnetic state is described by disordered local moment approach. In stoichiometric Ni 2 MnGa alloy, the total energy profile along the tetragonal deformation path differs between ferromagnetic ground state and paramagnetic state with high energy, where cubic structure of austenite exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…% of Zn are shown in figure 2(b), both magnetic states are related to the energy of the FM austenite of a given composition. The energy profile of Ni 2 MnGa in PM state exhibits a global minimum at c/a=1, whereas NM martensite is represented by a very shallow minimum with higher energy at (c/a) NM =1.14 in this magnetic state [34]. Doping on Mn sublattice has an even stronger suppressing effect on PM martensite and simultaneously lowers the austenite energy minimum, which predicts lower stability of FM states.…”
Section: Tetragonal Deformation In Pm Statementioning
confidence: 91%
See 1 more Smart Citation
“…% of Zn are shown in figure 2(b), both magnetic states are related to the energy of the FM austenite of a given composition. The energy profile of Ni 2 MnGa in PM state exhibits a global minimum at c/a=1, whereas NM martensite is represented by a very shallow minimum with higher energy at (c/a) NM =1.14 in this magnetic state [34]. Doping on Mn sublattice has an even stronger suppressing effect on PM martensite and simultaneously lowers the austenite energy minimum, which predicts lower stability of FM states.…”
Section: Tetragonal Deformation In Pm Statementioning
confidence: 91%
“…PM FM , has been established for Co and Cu-doping [24,33,34]. Both transformation temperatures can be theoretically predicted by more precise methods including phonon [35] or Monte Carlo [36] calculation, however, with much higher computational cost especially in the case of doped alloys.…”
Section: Introductionmentioning
confidence: 99%
“…A proper description of paramagnetic states with randomly oriented magnetic moments is difficult to achieve in ab initio models; thus, it is often approximated by all atoms having zero magnetic moments. [ 80,122 ] However, the stability of individual phases may differ in true paramagnetic states described by the CPA and the approximate nonmagnetic state, as illustrated in the study by Zelený et al [ 123 ] Qualitative predictions of changes in TnormalC caused by alloying can be based simply on the total energy difference between the paramagnetic and ferromagnetic states, as shown for doping by Co, Cu, [ 123 ] and Zn. [ 124 ] Calculations for noncolinear arrangements, such as spin spirals, can also be used to estimate TnormalC or magnon dispersion, [ 125 ] and more precise quantitative predictions of TnormalC can be performed if the magnetic exchange interaction parameters are exactly computed, which is possible for a wide composition range; [ 102,126–129 ] these results can serve as an input for Monte Carlo or spin dynamics simulations.…”
Section: Beyond a Perfect Lattice: Off‐stoichiometry Alloying And Ord...mentioning
confidence: 99%
“…Enkovaara et al [ 135 ] suggested that the strong MCA originates from the nonsymmetric surrounding of Ni atoms with a maximum in stoichiometric Ni2MnGa [ 135,136 ] . Although most of the works have focused only on stoichiometric alloys, [ 60,135–138 ] results for Mn‐excess and Co‐, Cu‐, [ 123 ] Zn‐, [ 124 ] or Pt‐doped alloys [ 139 ] are available in the literature, which predicted a decreased MCA with an increasing concentration of the alloying element in all cases. This trend was confirmed experimentally for Co‐ and Cu‐alloyed NM martensite [ 140 ] and partially for Fe‐alloyed NM martensite.…”
Section: Beyond a Perfect Lattice: Off‐stoichiometry Alloying And Ord...mentioning
confidence: 99%